2008
DOI: 10.1080/00379271.2008.10697583
|View full text |Cite
|
Sign up to set email alerts
|

Recherches sur la phylogénie du genreSaga(Orthoptera: Tettigoniidae): données chromosomiques

Abstract: Abstract. Studies on the phylogeny of the genus Saga (Orthoptera: Tettigoniidae): chromosomic data. Combining the fi rst cytogenetic analysis of four European Saga species, and the re-assessment of the karyotype of Saga pedo (Pallas 1771), with published data and the results of investigations in the fi eld, a phylogeny of the species included is proposed. The most ancestral karyotypes seem to be those of Saga ornata Burmeister 1839 and Saga cappadocica Werner 1903, with all autosomes being acrocentrics. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 6 publications
3
14
1
1
Order By: Relevance
“…For both subspecies of S. campbelli it is hypothesized that two Robertsonian translocations and one pericentric inversion, resulted in 2n = 27 (FN = 32) (two metacentric/submetacentric L1, L2 pairs and a subacrocentric X chromosome). The chromosome number of S. campbelli accords with the number recently reported by Lemonnier-Darcemont et al (2008). However, in our study an unexpected chromosome number of 2n = 23 was revealed in S. rammei.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…For both subspecies of S. campbelli it is hypothesized that two Robertsonian translocations and one pericentric inversion, resulted in 2n = 27 (FN = 32) (two metacentric/submetacentric L1, L2 pairs and a subacrocentric X chromosome). The chromosome number of S. campbelli accords with the number recently reported by Lemonnier-Darcemont et al (2008). However, in our study an unexpected chromosome number of 2n = 23 was revealed in S. rammei.…”
Section: Discussionsupporting
confidence: 91%
“…Cytogenetic differences between these species suggest that chromosomal divergence occurred during their speciation (Warcha owska-liwa et al, 2007). Lemonnier-Darcemont et al (2008) reached the same conclusion after studying of S. campbelli and S. rammei, which both have a chromosome number of 2n = 27%.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…Les autres paires formées, bien que provenant d'espèces diff érentes, ne montrent pas plus de diff érences que s'il s'agissait d'une espèce pure. Ceci montre bien que seule, une translocation robertsonienne sépare les caryotypes de S. hellenica et S. campbelli, comme déjà proposé (Lemonnier-Darcemont et al 2008).…”
Section: éTude Chromosomiqueunclassified